A sustainable vendor-buyer inventory model with incentives, green investment and energy usage under stochastic demand - Wakhid Ahmad Jauhari; Ivan Darma Wangsa; Hawa Hishamuddin; Novrianty Rizky (Cogent Business & Management)
This paper aims to minimize the emissions in the supply chain consisting of a vendor and a buyer under carbon regulations. Emissions from the supply chain are generated by several operations, namely production, transportation and storage, and are sought to be reduced by implementing a carbon tax policy. To cope with the carbon policy, the vendor is actively looking for the best strategy to reduce emission rates, one of which is by investing in green technology. Besides being able to reduce the amount of carbon produced, the investment made can also save the amount of energy needed in the production process. To support the investment, the government provides green incentives, the amount of which is determined based on the achievement of emission reduction targets. The objective of the proposed model is to simultaneously determine the review period, safety factor, number of shipments and green investment such that the joint total cost is minimised. An efficient method is developed in this paper to obtain the optimum solution for the model. A numerical example and a sensitivity analysis are provided to illustrate the application of the model and to examine the impact of key parameters on model behaviour and performance. The result indicates that the implemented green policies, namely carbon tax, green incentive and green investment, can improve the economic and environmental performances of the supply chain.